Addressing the cumulative impacts of multiple human pressures in marine systems, for the sustainable use of the seas - Borja, Angel; Elliott, Michael; Teixeira, Heliana; Stelzenmüller, Vanessa; Katsanevakis, Stelios; Coll, Marta; Galparsoro, Ibon; Fraschetti, Simonetta; Papadopoulou, Nadia; Lynam, Christopher; Berg, Torsten; Andersen, Jesper H.; et al. (Frontiers in Ocean Sustainability, 2024)
Human activities at sea have increased, causing subsequent degradation of ocean health and affecting ecosystem services and societal goods and benefits. Climate change further exacerbates the cumulative effects of these activities and their associated pressures.Hence, effective management of these multiple activities is imperative to ensure the sustainable use of the ocean. In response to these challenges, we have developed a comprehensive conceptual framework model within an ecosystem-based approach. This framework encompasses a versatile toolbox designed to assess cumulative pressures effects and the environmental status under the European Marine Strategy Framework Directive, in compliance with the Birds and Habitats Directives requirements and the need to secure the maintenance of ecosystem services and provision of societal benefits.Although we use European examples in the current discussion, we consider that there are similar challenges in many seas worldwide and so the recommendations here are widely applicable. Our aim is to facilitate the validation, harmonization, and demonstration of this toolbox across European regional seas and several countries, at different scales, from local to regional, including overseas territories. This approach aims to foster comparability in environmental status assessments. We anticipate that the proposed methodologies will serve as a foundational benchmark against which progress can be assessed in line with expectations and policy requirements. Additionally, this work prepares the groundwork for the forthcoming evaluation of the suitability, robustness, and applicability of these solutions and tools, thereby assisting managers in achieving Good Environmental Status (GES), both in European and wider global contexts, to address challenges which are common worldwide.